Toll-like receptor 2 (TLR2) plays a role in controlling cutaneous leishmaniasis in vivo, but does not require activation by parasite lipophosphoglycan. Issue 1 (December 2016) - Halliday, Alice; Bates, Paul; Chance, Michael; Taylor, Mark
Abstract Background Leishmaniasis is a neglected tropical disease affecting millions of individuals worldwide. Despite several studies reporting involvement of the innate immune receptor Toll-like receptor 2 (TLR2) in the recognition of surface glycolipids fromLeishmania parasites in vitro, the role of TLR2 and its co-receptors during cutaneous leishmaniasis infection in vivo is unknown. Methods To explore the role of TLR2 and its co-receptors in cutaneous leishmaniasis, mice deficient in either TLR2, 4, 1 or 6, or wild-type (WT) controls, were infected with eitherLeishmania major promastigotes, L. mexicana promastigotes, L. mexicana amastigotes, orLPG1 −/− L. mexicana promastigotes. For each infection, lesion sizes were monitored and parasite burden was assessed at various time points. To assess immune responses, draining lymph node (DLN) cells were re-stimulated with parasite antigens and the production of cytokines and parasite-specific antibody isotypes in blood was determined by ELISA. Results Mice deficient in TLR2 and TLR4 presented with larger lesions and higher parasite burdens than WT controls. Mice lacking TLR2 co-receptors TLR1 or TLR6 did not show exacerbated infection, suggesting that TLR2 does not require either co-receptor in the recognition ofLeishmania infection. Furthermore, it appears that lipophosphoglycan (LPG) is not the major mediator of TLR2 activation during infection withL. mexicana, as parasites lacking LPG (axenic amastigotes andLPG1 −/− promastigotes) also resulted in exacerbated disease in TLR2−/− mice. Infected TLR2−/− mice show a skewed Th2 immune response toLeishmania parasites, as demonstrated by elevated IL-4, IL-13 and IL-10 production by DLN cells fromL. mexicana infected mice in response to antigen. Furthermore, L. major infected TLR2−/− mice have elevated antigen-specific IgG1 antibodies. Conclusions TLR2 deficiency leads to exacerbation of disease and parasite burden through promotion of Th2 immunity. TLR2 activation in vivo occurs independently of parasite LPG, suggesting other parasite ligands are involved in TLR2 recognition ofLeishmania .